Utilization of Comprehensive Geriatric Assessment (P3G) in Primary Health Center at Medan City and Deli Serdang District of North Sumatera Province Indonesia 2018 - Boy, Elman; Pinem, Alfi Syahri; Ulfa, Aulia; Putri, Bonita Iravany; Pahlawati, Devi; Adedra, Ivando; Hutapea, Krisna Syahputra; Ramadani, Raudatul Popy; Pertiwi, Retno; Chan, Rika Karim; et al. (International Journal of Human and Health Sciences (IJHHS), 2019)
Introduction: The Ministry of Health of the Republic of Indonesia has issued a guide to Comprehensive Geriatric Assessment (P3G) in 2017, but there is few data regarding its use in health care institutions. The primary primary health center as the spearhead of primary services always receives geriatric patients and should have taken advantage of CGA. Objective: To find out the results of using a comprehensive assessment guide for geriatric patients in Medan City Primary health center and Deli Serdang District Primary health center in 2018. Methods: Descriptive study with cross sectional design, respondents were elderly who sought treatment in three primary health center such as Sukaramai Primary health centers in Medan City, Bandar Khalipah Primary health center and Tanjung Rejo Primary health center Deli Serdang District from 27 August to 20 September 2018 by determining the number of respondentss using the Slovin method, data collection by questionnaire interviews and data analysis using SPSS. Results: A respondents of 120 people were obtained, with an advanced category elderly aged 60-74 years at 90.8%, old aged 75-90 years at 8.3% and very old aged > 90 years at 0.9%. With ADL examination, respondents experienced mild-moderate dependence 60.8%, 37.5% independent, 1.7% heavy dependence. By examining the respondents’ IADL 89.2% independently, 0.8% was done by others, 0.8% needed help all the time, and 9.2% needed occasional assistance. By checking the risk of falling, 57.5% of the respondents experienced a low risk, 35% high risk and 7.5% there was no risk. With GDS examination 67.5% of 1respondents had no depression, 32.49% were most likely to have depression. With the Mini- Cog examination 78% of normal respondents, 21.7% suspected cognitive function decreased. With MMSE examination 80.8% of normal respondents, 16.7% of mild cognitive function disorders, and 2.5% of severe cognitive dysfunction. With AMT examination 73.3% of normal respondents and 26.7% of moderate memory disorders. With MNA screening screenings, 66.7% of respondents had no risk, and 33.3% might experience malnutrition and further study was needed. Based on the assessment of advanced MNA 95% risk of malnutrition, and 5.0% malnutrition. Conclusion: Elderly people who came to the primary health center most were elderly aged 60-74 years at 90.8%, the highest gender was women at 53.3%, based on the ADL examination, the respondents experienced the most mild-moderate dependence of 57.7%, IADL examination amounting to 89.2% independently did not need assistance, risk checking fell by 57.5% respondents experienced a low risk of falling, GDS examination amounted to 67.5% of respondents had no depression, Mini- Cog examination of 78% of respondents did not experience a decline cognitive function, MMSE examination of 80.8% of respondents did not experience cognitive impairment, AMT examination was 73.3% of respondents did not experience memory impairment, MNA examination of 66.7% did not experience malnutrition. International Journal of Human and Health Sciences Vol. 03 No. 02 April’19. Page: 88-100